Bilateral Posterior Uveitis and Retinal Detachment During Immunotherapy: A Case Report and Literature Review - Peng, Ling; Mao, Qi-Qi; Jiang, Bo; Zhang, Jin; Zhao, Yi-Lei; Teng, Xiao-Dong; Yang, Jin-Song; Xia, Yang; Chen, Shi-Qing; Stebbing, Justin; Jiang, Hai (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors (ICIs) cause fewer toxicities than conventional chemotherapy. Although most of the immune-related adverse events (irAEs) are mild, reversible, and manageable, potentially severe and rare irAEs remain relevant. We present a 24-year-old man with advanced hereditary renal cancer who developed bilateral posterior uveitis and retinal detachment after systematic treatment of ICI and an anti-angiogenic drug. Axitinib and pembrolizumab were administered with a partial response and following the severe ocular irAE and systemic corticosteroid treatment was initiated. Our case indicates that ocular irAEs may occur rapidly. To the best of our knowledge, this is the first case of posterior uveitis and retinal detachment in hereditary renal cancer patients treated with ICI and anti-angiogenic drugs.